2016
DOI: 10.1080/15402002.2016.1188391
|View full text |Cite
|
Sign up to set email alerts
|

Sleep Duration in Relation to Attention Deficit Hyperactivity Disorder in American Adults

Abstract: Attention deficit hyperactivity disorder (ADHD) is a neurodevelopmental condition being diagnosed in increasing numbers. While the link between sleep and ADHD is of increasing interest, the relationship between sleep duration and ADHD remains largely uninvestigated in adult populations. We evaluated the association between self-reported sleep duration and ADHD in a cohort of American adults using data from the 2012 National Health Interview Survey (Centers for Disease Control and Prevention, 2012). Of the 30,8… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 38 publications
0
14
1
Order By: Relevance
“…In clinical practice, sleep problems are reported in an estimated 25%–50% of individuals who have ADHD,46 and adults who do not get the recommended amount of sleep are more likely to report ADHD symptoms 7. Sleep disturbances in such individuals have been associated with comorbid primary sleep issues and/or alterations associated with the medications used to treat ADHD 8.…”
Section: Introductionmentioning
confidence: 99%
“…In clinical practice, sleep problems are reported in an estimated 25%–50% of individuals who have ADHD,46 and adults who do not get the recommended amount of sleep are more likely to report ADHD symptoms 7. Sleep disturbances in such individuals have been associated with comorbid primary sleep issues and/or alterations associated with the medications used to treat ADHD 8.…”
Section: Introductionmentioning
confidence: 99%
“…Our finding replicates the large population study of Bogdan and Reeves, although they did not correct for comorbid affective disorder. 14 In other clinical studies, ADHD patients reported shorter sleep duration than controls. 40,41 When sleep duration was objectively measured, it was found to be normal in three studies.…”
Section: Discussionmentioning
confidence: 88%
“…A very large population study (n = 30,858; ADHD cases n = 1,122) found that both increased and decreased sleep duration were associated with increasing odds of reporting ADHD symptoms. 14 Two other studies reported a mean total sleep duration less than 6 hours in adults with ADHD 15,16 ; however, the latter included a very small ADHD sample (n = 24). In contrast, in three small studies (ADHD samples n = 20-40) measuring total sleep duration objectively using actigraphy or polysomnography, no significant difference in sleep duration was found between those with ADHD and healthy controls.…”
Section: Scientific Investigationsmentioning
confidence: 98%
“…Interestingly, the rs301806 was previously found in the MFA for total ADHD symptoms, suggesting the shared contribution of genetic mechanisms between total ADHD symptoms and inattention domains. Furthermore, the involvement of PER1 gene in the influence of sleep duration and circadian regulation (Hida et al, ; Husse, Hintze, Eichele, Lehnert, & Oster, ) could be seen as an interesting finding due to the prevalence of sleep problems in ADHD individuals (Bogdan & Reeves, ; Cassoff, Wiebe, & Gruber, ), especially for inattention domains (Gruber et al, ).…”
Section: Discussionmentioning
confidence: 99%